Efficacy analysis of electroacupuncture plus TDP in the treatment of peripheral facial paralysis: a systematic review and meta-analysis - Gao, Hua-Wei; Xia, Qing-Chang; Li, Zhi-Hong; Chen, Wei; Lu, Yan (Frontiers in Neurology, 2024)
ObjectiveThis study intends to carry out a systematic review and meta-analysis of electroacupuncture combined with TDP in the treatment of peripheral facial paralysis.MethodsCNKI, VIP, Wanfang, PubMed, Embase and Cochrane databases were searched for literatures on randomized or quasi-randomized controlled trials of electroacupuncture combined with TDP in the treatment of peripheral facial paralysis, and the references of the included studies were searched. Meta-analysis was performed using Stata15.0 software after risk of bias, quality assessment, and data extraction of the included articles by two reviewers independently.ResultsFifteen articles were finally included, with approximately 1,568 participants (920 in the treatment group and 648 in the control group). Meta-analysis showed that the effective rate of electroacupuncture combined with TDP in the treatment of peripheral facial paralysis was not significantly different from other treatment methods ([RR = 1.05, 95%CI (0.97, 1.12), p = 0.226]), and the recovery rate was better than other treatment methods ([RR = 1.14, 95%CI (1.05, 1.24), p = 0.002]). Subgroup analysis showed that when stratified by the inclusion of minors in the study population, it was observed that in studies including minors, the combination of electroacupuncture and TDP therapy demonstrated superior efficacy in treating peripheral facial paralysis compared to other therapeutic modalities [OR = 1.14, 95% CI (1.03, 1.25), p = 0.011]. Conversely, in studies where the population comprised solely adults, no significant difference was found between the combination therapy and other treatments [OR = 1.15, 95% CI (0.99, 1.33), p = 0.059]; whether electroacupuncture alone or other treatment methods, the recovery rate of electroacupuncture combined with TDP in the treatment of peripheral facial paralysis was better than other methods.ConclusionElectroacupuncture combined with TDP is superior to other treatment methods in the treatment of peripheral facial paralysis.